Step it up: A multicomponent intervention to increase stair use in a university residence building - Howie, Erin; Young, D. (American Journal of Health Promotion, Inc., 2011)
Purpose. Examine the effects of a multicomponent intervention on stair usage. Design. Nonrandomized controlled intervention. Setting. Two multistory university dormitories. Subjects. Total of 5711 direct observations of university dormitory residents. Intervention. The 2-week "Step It UP" intervention used poster prompts and fun/ competitive challenges with incentives to encourage residents to take the stairs instead of the elevators. Measures. Ascending stair and elevator use was directly observed and coded for gender at high traffic times in intervention and control dormitories for 14 nonconsecutive hours over 1 week each at baseline, midintervention, and 1 week postintervention. Analysis. The proportions of ascending stair and elevator users were compared using ? 2 analyses. Results. Baseline stair use was equal between intervention and control dormitories (24.9% and 27.8%, respectively; ? 2 [1, N = 1849] = .08; p = .77). Stair use significantly increased from baseline in the intervention dormitory to 33.24% (? 2 [1, N = 2192] = 18.44; p, .001) compared with no change in the control. Stair use returned to baseline in the intervention dormitory at postintervention (25.4%; ? 2 [1, N = 2297] = .08; p = .78). There were no significant differences between genders. Conclusion. This multicomponent, short-duration intervention significantly increased stair usage in a university dormitory relative to the control but was unable to sustain the increase when prompts were removed. Campaigns to sustain stair use are needed. Formative assessment is required to determine what combinations of components may yield the most cost-effective approach for future interventions. Copyright © 2011 by American Journal of Health Promotion, Inc.